Introduction to the thematic issue: Reflections on religion in Argentina. Churches, the State and society (19th and 20th centuries) (Quinto Sol, 2015)
This dossier includes papers by Ignacio Martínez, Paula Seiguer, Diego Mauro and Mariano Fabris